2014
DOI: 10.2298/sarh1404226r
|View full text |Cite
|
Sign up to set email alerts
|

Urgent hybrid approach in treatment of the acute myocardial infarction complicated by the ventricular septal rupture

Abstract: In selected cases, with high operative risk and unstable hemodynamic state due to AMI complicated by VSR, urgent hybrid approach consisting of the initial PCI followed by surgical closure of VSR may represent an acceptable treatment option and contribute to the treatment of this complex group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For high-risk, hemodynamically unstable VSR and cardiogenic shock, the recommended treatment is initial percutaneous coronary intervention (PCI) of the infarct-related artery, followed by immediate surgical closure of the ventricular septal rupture. This approach is expected to quickly establish blood flow and reduce the risks, time, and complexity of the urgent cardiosurgical intervention [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For high-risk, hemodynamically unstable VSR and cardiogenic shock, the recommended treatment is initial percutaneous coronary intervention (PCI) of the infarct-related artery, followed by immediate surgical closure of the ventricular septal rupture. This approach is expected to quickly establish blood flow and reduce the risks, time, and complexity of the urgent cardiosurgical intervention [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for the mentioned difference was the other treatment strategy for each patient, dictated by the clinical symptoms. Radosavljević-Radovanović et al [29] found that despite improved treatment, surgical technique and percutaneous revascularization, the mortality rate ranged from 24% to 87%. The patients treated pharmacologically showed an even greater mortality rate -90%.…”
Section: Treatment Methods and Survival Of Patients With Mechanical Comentioning
confidence: 99%
“…(1,2) Its mortality rate is 24-87% and 90% in patients with and without definitive surgery, respectively. (3,4,5) Defect size, hemodynamic status, and comorbidities may predispose the mortality on VSR cases. (3,4) Surgical closure should be performed immediately in large VSRs (≥ 15 mm) to prevent embolizations.…”
Section: Introductionmentioning
confidence: 99%
“…(3,4,5) Defect size, hemodynamic status, and comorbidities may predispose the mortality on VSR cases. (3,4) Surgical closure should be performed immediately in large VSRs (≥ 15 mm) to prevent embolizations. Meanwhile, amplatzer closure is recommended for small-medium VSRs ≤15 mm to stabilize the patients' hemodynamic and may also be used as a temporary correction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation